Highly Stretchable and Flexible Melt Spun Thermoplastic Conductive Yarns for Smart Textiles - G. M. Nazmul Islam; Stewart Collie; Muhammad Qasim; M. Azam Ali (Nanomaterials, 2020)
This study demonstrates a scalable fabrication process for producing biodegradable, highly stretchable and wearable melt spun thermoplastic polypropylene (PP), poly(lactic) acid (PLA), and composite (PP:PLA = 50:50) conductive yarns through a dip coating process. Polydopamine (PDA) treated and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) coated conductive PP, PLA, and PP/PLA yarns generated electric conductivity of 0.75 S/cm, 0.36 S/cm and 0.67 S/cm respectively. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the interactions among the functional groups of PP, PLA, PP/PLA, PDA, and PEDOT:PSS. The surface morphology of thermoplastic yarns was characterized by optical microscope and Scanning Electron Microscope (SEM). The mechanical properties of yarns were also assessed, which include tensile strength (TS), Young’s modulus and elongation at break (%). These highly stretchable and flexible conductive PP, PLA, and PP/PLA yarns showed elasticity of 667%, 121% and 315% respectively. The thermal behavior of yarns was evaluated by differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA). Wash stability of conductive yarns was also measured. Furthermore, ageing effect was determined to predict the shelf life of the conductive yarns. We believe that these highly stretchable and flexible PEDOT:PSS coated conductive PP, PLA, and PP/PLA composite yarns fabricated by this process can be integrated into textiles for strain sensing to monitor the tiny movement of human motion.